The Aesthetic Value of the Accompaniment Music of the Dance Drama 'The Blessing of Siva-Visvapujita' | Nilai Estetika Musik Iringan Drama Tari “The Blessing of Siva-Visvapujita” - Dewi Yulianti Ni Ketut; I Ketut Sariada; I Made Marajaya (GHURNITA: Jurnal Seni Karawitan, 2024)
Music is an art form consisting of sounds arranged in certain patterns to produce compositions containing harmony, melody, and rhythm. Accompaniment music accompanies an activity or event, such as art performances, dances, dance dramas, films, ceremonial events, or daily activities. This paper aims to find aesthetic values in the musical accompaniment influences the dance drama The Blessing of Siva-Visvapujita and find out how the musical accompaniment influences the interpretation and delivery of the story in the dance drama The Blessing of Siva-Visvapujita. This research applies a qualitative descriptive method, which consists of three stages, namely (1) Data collection, (2) Data analysis, and (3) Presentation of analysis results. This research shows that the musical accompaniment to the dance drama The Blessing of Siva-Visvapujita contains aesthetic values with unique melodic beauty and harmony, as well as rhythm and dynamics that suit the storyline and character traits. Synchronization with the dance choreography creates a harmonious experience while expressing emotion and atmosphere through music enriches the aesthetic dimension. The use of MIDI technology brings innovation to the listening experience. Music also plays an important role in creating atmosphere, highlighting emotions and conflict, and strengthening the narrative in the performance as a whole.